Legal Aspects of use of QR Codes as a Tool of Payment in Cross Countries - Tanto, Harnando; Pakpahan, Kartina; Pakpahan, Elvira Fitriyani (IJBLE Scientific Publications Community Inc., 2025)
Bank Indonesia stated that currently QR-Code Indonesia can be used in Southeast Asia and Asian countries, better known as QR-Codecross border or QR-Code across countries. Bank Indonesia as the banking regulator in Indonesia continues to promote the use of QR-Codecross border as a substitute for currency. physical money so that it can be used by people who travel abroad or tourists to Indonesia and/or people who carry out cross-border transactions, but on the other hand there are no special regulations yet to ensure the security and comfort of the public in using QR-Code across borders. The research method uses a type of normative juridical research, namely research that focuses on the study of legislation and how the law works. The data collection method uses the library research method or library research using secondary data in the form of legislation, books and previous research using the descriptive analysis method. Analysis The form of QRIS regulation between countries is an agreement outlined in the form of an MoU cooperation document. There are 5 central banks that have signed, namely Bank Indonesia, Bank Negara Malaysia, Bangko Sentral Pilipinas, Monetary Authority of Singapore, and Bank of Thailand. Currently, its use is only based on a cooperation agreement between Bank Indonesia and the Central Bank of a foreign country or the provision of foreign payments. Regulations for cross-border QRIS use in Indonesia are currently only based on the Regulation of Members of the Board of Governors Number 21/18/Padg/2019 concerning the Implementation of the National Quick Response Code Standard for Payments.